ANALISIS YURIDIS PERTIMBANGAN HAKIM DALAM KASUS JUAL-BELI YANG DIKENAKAN PASAL 480 KUP (STUDI KASUS: PUTUSAN NOMOR 1291/PID.B/2018/PN.JKT.PST) - Hendy Hendy; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2019)
Dewi Sri Astuti, initially she was only trying to increase financial resources in the family, but she tripped over a case experienced by her business partners, namely Suherman and Susanti. Dewi Sri Astuti was charged guilty because she had purchased items resulting from the theft of a crime committed by her business partners in the place where they worked. Even though Dewi Sri Astuti did not know that the goods she had received from her business partners were the result of a criminal act of theft. In this case to be able to convict someone must be fulfilled two things, namely as actus reus (physical element) and.mens.rea (mental element). However, Dewi Sri Astuti was still found guilty even though it did not fulfill the subjective element of the crime. How is the juridical analysis of buying and selling actions that are subject to article 480 of the Criminal Code (case study: verdict number 1291 / Pid.B / 2018 / PN.JKT.PST)? The author used normative legal methods and used interview data as supporting data. The.results of the study revealed that Dewi Sri Astuti did not fulfill all the elements in Article.480 of the Criminal.Code, where in the element of criminal offense there are 2 (two) elements. First.element is an objective element and.the second element.is a subjective element.